1985
DOI: 10.1111/j.1600-0528.1985.tb00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social class and fluoridation on child dental health

Abstract: In this study in oral epidemiology, officially collected statistics are presented which show that, 15 yr after fluoridation commenced in Auckland, New Zealand, there was still a significant correlation between dental health of children and their social class. They also show that treatment levels have continued to decline in both fluoridated and unfluoridated areas, and are related to social class factors rather than to the presence or absence of water fluoridation. In the unfluoridated areas all the children, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…[8][9][10][11] These findings have been confirmed using a number of different deprivation indices. 12,13 However, a review of the literature shows a number of studies which show no differential benefit of fluoridation to more deprived children and some which show the opposite effect.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…[8][9][10][11] These findings have been confirmed using a number of different deprivation indices. 12,13 However, a review of the literature shows a number of studies which show no differential benefit of fluoridation to more deprived children and some which show the opposite effect.…”
supporting
confidence: 52%
“…17 Another author contradicted his own earlier conclusions of more benefit to deprived children 9 after reworking data and adding new data on treatment provision. 18 In addition to obvious selection bias in relying on treatment data, the report has been criticised for using different measures of social class over time and ignoring cross border flow in school attendance. The large annual variation in treatment provided per child also casts doubt on the validity of using quantity of treatment as a proxy for disease.…”
Section: Social Classmentioning
confidence: 99%
“…Although tnatiy studies (13,14,19,20) have shown that these differences between soeial classes remained even when water was fluoridated, sotne studies have shown that fluoridation had the greatest relative itnpact on the high caries level found in the lower social class children (21,22).…”
mentioning
confidence: 99%
“…The lack of any marked difference in this study might be due to the fact that these children live in an area with optimal fluoride supply. Water fluoridation seems to be the environmental factor that has greatest influence in reducing class differences (Colquhoun 1977). However, fluoride is insufficient to obviate the influence of social background on caries experience (Bradnock et al 1984, Carmichael et al 1980, Colquhoun 1985.…”
Section: Social Classmentioning
confidence: 98%